Reduced Cell-Free Mitochondrial DNA Levels Were Induced by Antipsychotics Treatment in First-Episode Patients With Schizophrenia - Ouyang, Houxian; Huang, Minfang; Xu, Yongming; Yao, Qin; Wu, Xiangping; Zhou, Dongsheng (Frontiers in Psychiatry, 2021)
Cell-free mitochondrial DNA (cf-mtDNA) is a damage-associated molecular pattern that boosts the release of cytokines and induces the body’s immune response; therefore, it is closely related to mental diseases. The aim of this study is to evaluate a potential link between cf-mtDNA and clinical progression in first-episode schizophrenic patients. In this study, plasma cf-mtDNA levels in 34 first-episode schizophrenic patients before and after 8 weeks of antipsychotic treatment were examined. In addition, the clinical progression of first-episode schizophrenia was assessed using the Positive and Negative Syndrome Scale (PANSS). The copy-number changes in the plasma cf-mtDNA (Δcf-mtDNA) were significantly correlated with changes in the PANSS scale scores (ΔPANSS) in first-episode schizophrenic patients (ΔPANSS total score, P=0.002; ΔPANSS positive score, P=0.01). Plasma cf-mtDNA may represent a relevant tool in the future to assist in the assessment of clinical progression in first-episode schizophrenic patients.